Philosophical Presentations of Raising Children The Grammar of Upbringing - Hodgson, Naomi; Ramaekers, Stefan; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This book uses contemporary film to articulate a philosophical account of raising children. It forms part of a revaluation of the parent as a pedagogical figure, which stands in contrast to the instrumental accounts dominant in contemporary 'parenting' culture. Hodgson and Ramaekers use film in order to offer an affirmative account of the experience of raising children, as a presentation of those inevitable aspects and experiences that upbringing is: the initiation into language and the world; the representative nature of the parent; and the maintaining of mundane practices that constitute our shared culture and community. The films which are discussed are taken as grammatical investigations and enable the authors to develop an account of the use of film in education and as educational philosophy, and to respond to each film's invitation to articulate the existential dimensions of raising children. Philosophical Presentations of Raising Children will be of interest to students and scholars across a range of disciplines, including education, sociology, philosophy, critical parenting studies and film studies.
Part I: Philosophical background -- 1. Parenting, upbringing, and educational philosophy -- 2. The educational force of film: Presentations of upbringing -- Part II: The films -- 3. The Seventh Continent: Taking care and making family -- 4. Dogtooth: Initiating children in language and world -- 5. Le Fils: (Re)Turning and assembling Reminders -- Part III: Postscript -- 6. Towards a pedagogical understanding of upbringing. .
Keywords: Sociology; Social groups; Motion pictures; Television broadcasting; Education -- Philosophy; Sociology of Family, Youth and Aging; Film and Television Studies; Philosophy of Education